Resveratrol activates CD8+ T cells through IL-18 bystander activation in lung adenocarcinoma - Zhang, Wei; Zhang, Ruohao; Chang, Zhiguang; Wang, Xiaobo (Frontiers in Pharmacology, 2022)
Resveratrol, as a natural product, has been identified its anti-tumor effect in various kinds of tumor type, including colon cancer, breast cancer, pancreatic cancer. Most of these research focus on the inhibitory effect of resveratrol on tumor cells themselves, and there is less research about resveratrol effect tumor immunology. In this study, we found that resveratrol could inhibit the growth of lung adenocarcinoma subcutaneous tumor model by using β-cyclodextrin-resveratrol inclusion complex. After resveratrol treatment, the proportion of M2-like tumor associated macrophage was reduced and tumor infiltrating CD8T cells were activated significantly. Base on co-culture experiment and antibody neutralization experiment, we found that macrophage-derived IL-18 may the one of key cytokine in resveratrol anti-tumor effect for CD8T cell activation. In this paper, we showed a novel angle of view of resveratrol tumor suppressive mechanism, nature product could reprogram tumor associated macrophage and CD8T effector cells for tumor treatment.